Proses Penyajian Kolaborasi Angklung dan Orkestra pada Aransemen Lagu Radetzky March Di SD Budi Mulia Dua Yogyakarta - Wahyudi Wahyudi; Ayub Prestiyo (Institut Seni Indonesia Yogyakarta, 2015)
This researcch is focused on musical arrangement of the angklung and orchestra collaborative performcance process as a part of the Yogyakarta Second Budi Mulia Primary School extra curricular project. It is done within qualitative research frame work, and specifically approached through developmental method. That is a research process that study its subject as musical practitioners. This study concludes that the collaborative work of the angklung and orchestra would contribute to an interesting and innovative performance if it is supported by a good musical arrangement which is based on the angklung registers and the motoric skills of children